Evaluation of the response rate of chemo-radiation and brachytherapy in patients with locally advanced carcinoma cervix in a tertiary care center - Semwal, Sukanya; Sethi, Jaskaran S.; Gairola, Munish; Simson, David K.; Kumar, Rajendra; Goyal, Ankit; Vashistha, Apoorv; Kumar, Ankit; Goel, Palak (International Journal of Research in Medical Sciences, 2020)
Background: Incidence and mortality estimates are used to measure the burden of cancer in a population and survival estimates are ideal for evaluating the outcome of cancer control activities. Survival studies evaluate the quality and quantity of life of a group of patients after diagnosing the disease. The patient survival after the diagnosis of cervical cancer is indirectly influenced by socio-economic factors. The present study was carried out with an aim to evaluate the success rate of chemo-radiation followed by brachytherapy to the patients of locally advanced carcinoma (Ca.) cervix in a tertiary care center. Methods: All cases were staged according to the International Federation of Gynaecologists and Oncologists (FIGO) staging system. To illustrate the observed survival of cancer patients Kaplan-Meier curve was plotted. All the patients, except one, completed chemo-radiation and were retrospectively analyzed for the presence of local residual disease, local recurrence, distant metastases, radiation reactions, disease-free survival, and overall survival. Results: There were 22 patients of Carcinoma cervix reported in the radiation oncology department in the year 2018 and 2019. The overall treatment time ranged from 30 days to 178 days, with a median of 63 days. All the patients had a complete response after the treatment. The median follow-up time for all the patients was 15 months. Three patients had a metastatic recurrence and one patient developed distant metastases as well as local recurrence. Overall survival rate was 100% while the disease-free survival rate was 81.82%. Conclusions: The response to chemo-radiation in the treatment of locally advanced Carcinoma cervix is comparable to historic data and is well tolerated.